Investigating the implant position reproducibility of optical impressions obtained using an intraoral scanner and 3D-printed models fabricated using an intraoral scanner - Maya Iwamoto; Wataru Atsuta; Yasuhide Kaneko; Junnosuke Ito; Takeshi Kanno; Takahiro Murakami; Jyoji Tanaka (SpringerOpen, 2023)
Abstract Purpose This study aims to examine the effect of the size of the intraoral scanning area on implant position reproducibility and compare the implant position reproducibility of plaster models fabricated using the silicone impression technique, the digital model of an intraoral scanner, and three-dimensional (3D)-printed models fabricated using an intraoral scanner. Methods Scanbodies were attached to an edentulous model with six implants (master model) and were scanned using a dental laboratory scanner to obtain basic data. The plaster model was fabricated using the open-tray method (IMPM; n = 5). The master model was then scanned in various implant areas using an intraoral scanner to obtain data (IOSM; n = 5); the scanning data of six scanbodies were used to fabricate the 3D-printed models (3DPM; n = 5) using a 3D printer. Scanbodies were attached to the implant analogs of the IMPM and 3DPM models and data were obtained using a dental laboratory scanner. The basic data and IMPM, IOSM, and 3DPM data were superimposed to calculate the concordance rate of the scanbodies. Results The concordance rate of intraoral scanning decreased as the number of scanbodies increased. Significant differences were observed between the IMPM and IOSM data, and between the IOSM and 3DPM data; however, the IMPM and 3DPM data did not differ significantly. Conclusions The implant position reproducibility of the intraoral scanner decreased with an increase in the scanning area. However, ISOM and 3DPM may provide higher implant position reproducibility than plaster models fabricated using IMPM.